Does difference in secondary and tertiary literacy influence life insurance consumption in the selected ASEAN countries? - Lee, Hui Shan; Low, Kevin Lock Teng; Chong, Shyue Chuan; Sia, Bik Kai (School of Computing, College of Arts and Sciences, Universiti Utara Malaysia, 2016)
Life insurance as financial tool has played essential roles to both individual and economy with the functions of promoting long term saving, reinvestment of funds, risk management, development of capital markets support on economic growth. The determinants of life insurance consumption in the perspective of economics and demographic are to be examined in the ASEAN context. The study on the difference of secondary and tertiary education towards demand for life insurance is investigated to highlight the importance of introducing insurance knowledge in the education syllabus to improve future economics with better income and social return with the support of life insurance in the market. This will ensure a well risk management among individuals, firms and countries as a whole and it align with the AEC blueprint with the purpose to rise up the living of the community.